Adipose tissue: an inflammatory organ that can not be ignored in periodontal disease related to obesity - Wang, Qiqi; Li, Hongyan; Huan, Yu; Zhou, Tianyu; Zhang, Jingdan; Fang, Rongkaixuan; Sun, Yue; A, Lan; Xu, Wenzhou (Frontiers in Immunology, 2025)
In obesity, the pathological remodeling of adipose tissue characterized by hyperplasia and hypertrophy serves as a critical hub driving chronic inflammation. This process triggers adipose microenvironment disruption, manifesting as reduced angiogenesis, excessive extracellular matrix deposition, dysregulated adipokine secretion, and enhanced immune cell infiltration, ultimately leading to a systemic low-grade inflammatory state. Functioning as an active inflammatory organ, dysfunctional adipose tissue specifically exacerbates periodontitis progression through multiple mechanisms: including glucose/lipid metabolic imbalance, dysregulated bone metabolism with imbalanced osteoclast-osteoblast activity, immunometabolic disturbances, microcirculatory impairment, degradation of periodontal extracellular matrix and dysfunction of epithelial barrier and gut microbiota dysbiosis. This review systematically elucidates the interactive mechanisms between adipose tissue-derived inflammatory signaling and periodontal pathology, emphasizing its central role in obesity-associated periodontal diseases. Based on these mechanisms, we propose targeted intervention strategies: modulating adipokine secretion, suppressing immune cell infiltration in adipose tissue or restoring adipose tissue metabolic homeostasis may emerge as novel approaches to disrupt the obesity-periodontitis vicious cycle.Future studies might enhance the clinical translation of multi-organ treatment approaches that target the adipose tissue-periodontium axis while continuing to explore the regulatory effects of immune pathways specific to adipose tissue on the periodontal microenvironment.